In vivo and in silico study of europinidin against streptozotocin-isoproterenol-induced myocardial damage via alteration of hs-CRP/CPK-MB/Caspase-3/Bcl-2 pathways - Khalid Saad Alharbi; Muhammad Afzal; Fahad A. Al-Abbasi; Ehssan Moglad; Salwa D. Al-Qahtani; Naif A. R. Almalki; Faisal Imam; Nadeem Sayyed; Imran Kazmi (Scientific Reports)
Abstract Europinidin is a novel anthocyanidin found in the petals of Plumbago europea that exhibits several physiological effects. Research was conducted to assess europinidin’s cardioprotective efficacy in a diabetic and myocardial infarction (MI) experimental model. Rat was injected through the intraperitoneal administration of 45 mg/kg of streptozotocin (STZ), while MI was induced by subcutaneously administering 85 mg/kg of isoproterenol (ISP) at 24 and 48 h prior to the sacrifice procedure. Europinidin 10 and 20 mg/day was administered orally for 4 weeks after validation of diabetes (glucose > 250 mg/dl) on the 7th day. Experimental rats were randomly allocated to control, STZ-ISP control, STZ-ISP + europinidin-10 mg, STZ-ISP + europinidin-20 mg and europinidin 20 mg perse group. Biochemicals parameters including anti-diabetic (Glucose, HbA1c, serum insulin), cardiac markers (hs-CRP, CPK-MB), dyslipidaemia (lipid analysis), anti-inflammatory (IL6, TNF-α and IL-β), oxidative stress (MDA) and antioxidant (SOD, CAT and GSH), kidney function (creatinine), liver function (AST) and pancreatic function (lipase) along with apoptosis markers (Bcl-2, caspase-3) were evaluated. In addition, histopathological indices of heart injury were investigated. In addition, molecular docking (AUTODOCK Tools 1.5.6.) and dynamics were performed. Europinidin (10 and 20 mg/day) reduced blood glucose, HbA1c, hs-CRP, and CPK-MB. It improved serum insulin, blood lipid profile and reduced inflammatory cytokines (IL-6, TNF-α, IL-β), oxidative stress and increased antioxidant enzymes (SOD, CAT and GSH). Europinidin also protected renal, hepatic functions and restored apoptosis markers (increased Bcl-2, decreased caspase-3 levels). Histopathological analysis demonstrated a reduced extent of myocardial necrosis and fibrosis. Europinidin binds in silico to proteins 1NME, 1I0E, 3I2Y and 4AQ3 with energies of -7.038, -6.682, -8.6 and − 8.761 kcal/mol, respectively. While molecular dynamics simulation studies supported the interactions of europinidin with important therapeutic target proteins. Europinidin demonstrates significant cardioprotective and anti-diabetic potential in a diabetic MI experimental model.